‘The inclusive way’ hackathon – inclusive wayfinding and pedagogy - Moys, Jeanne-Louise; Hwang, Faustina; Marsili, Ugo; Nunes, Richard; Tagg, Adrian; Vasilikou, Carolina (InfoDesign, 2023)
This paper discusses the opportunities and challenges for learning about and building skills for inclusive practice through a two-day, multidisciplinary, collaborative hackathon. ‘The inclusive way’ brought together students and staff from different disciplines and study levels, people with disabilities and industry professionals. Working on-site, project teams explored an inclusive wayfinding brief, developing and appraising prototypes for inclusive practice in response to the physical site and its immediate surroundings. This presentation reflects on the hackathon as a pedagogic approach, highlighting its potential and limitations for communication and information design education in the 21st century.